The relationship between neuropsychological dispersion, processing speed and memory after electrical injury. Issue 2 (7th February 2021) - Paxton, Jessica L.; Resch, Zachary J.; Cation, Bailey; Lapitan, Franchezka; Obolsky, Maximillian A.; Calderone, Veroly; Fink, Joseph W.; Lee, Raphael C.; Soble, Jason R.; Pliskin, Neil H.
ABSTRACT: Introduction : Previous studies of neuropsychological performance in electrical injury (EI) patients have produced evidence of deficits in various cognitive domains, but studies have yet to investigate relationships among performance in cognitive domains post-EI. This study examined whether dispersion among neuropsychological test scores was associated with injury parameters and neuropsychological performance in EI patients. Additionally, we examined whether dispersion, processing speed and/or executive abilities explain variance in episodic verbal and visual memory performance among EI patients. Method: Data from 52 post-acute EI patients undergoing outpatient evaluation with objectively-verified valid neuropsychological test performance were examined. Tests included measures of verbal and visual memory, processing speed, and executive functioning. Dispersion was calculated from executive functioning and processing speed scores. Results: Dispersion was not related to mean performance or injury characteristics, but was significantly negatively correlated with performance on a test of processing speed, suggesting that increased dispersion is associated with reduced cognitive efficiency post-EI. Delayed visual memory was related to both dispersion scores and processing speed. Stepwise regression equations predicting delayed memory determined that processing speed most significantly predicted delayed visual memory, even after controlling for immediate visual memory. No significant relationships emerged between verbal memory and non-memory neuropsychological scores. Conclusions: This is the first study to examine neuropsychological dispersion and relationships among domains of cognitive functioning in EI. Current results suggested that neuropsychological dispersion is not a marker of general functioning or severity of injury in EI patients, but may represent more specific processing speed abilities. Processing speed predicts delayed visual memory performance in EI patients, which should be considered in interpreting test scores during evaluations.